EFFICIENCY OF WATER FILTERING PROCESS DEPENDING ON THE FILTER LAYER POROSITY AND FLOW - A MATHEMATICAL MODEL - OANA TIRTOACA IRIMIA; VALENTIN NEDEFF; MIRELA PANAINTE-LEHADUS; CLAUDIA TOMOZEI (Journal of Engineering Studies and Research)
Mathematical modeling represents a challenge for any researcher or engineers that working in the field of applied sciences. The experimental approach to the water filtering process allowed achieving and verification a three-dimensional mathematical model, depending on the intake flow of the filter, the porosity of the filter layer and the nature of the filter layer. The mathematical model was developed and verified using the software Table Curve 3D. It was found that the mathematical model proposed offers a viable and robust method for determining the mechanical filtration efficiency of water.